Assessment of Tree Species Diversity of Sitapahar forest Reserve, Cidttagong Hill Tracts (South) forest Division, Bangladesh - Nath, T. K.; Hossain, M. K.; Alam, M. K. (Indian Forester, 2000)
The paper describes the present tree stocks and speCIes diversity in four different compartments of Sitapahar Forest Reserve. Individual tree stems per hectare was highest in Compartment No. 28, whereas basal area per hectare was highest in Compartment No. 27. The Shannon-Weiner Diversity Index, Species Diversity Index, Richness Index and Evenness Index was highest in Compartment no. 51, but Index of Dominance was lowest in Compartment No. 51. Trends of diversity indices show that vegetation community in Compartment No. 51 is highly stable in comparison to remaining three compartments. The overall tree diversity in Sitapahar Forest Reserve is comparable to the tropical forests and emphasis was given to conserve the area.